Radiation Enviroment in Selected Healthcare Centers in Palestine - Asmaa Abd Alkareem Shehade (My University, 2016)
The dose rate for X, Gamma ray and beta radiation flux density inside the control room and waiting room in the X-ray rooms have been measured by using Radiation moinitor, the measurements has been taking in the staff places, and at a height of 1 meter from the surface of the earth. The measured values of X-ray radiation dose were less than the maximum permissible dose for worker adopted by the Palestinian Ministry of Health in all tested rooms. The values of power flux density for frequency ranged from 200MHz up to 8 GHz, in some healthcare centers in Palestine have been measured by using Acoustimeter. The average values of measured power flux density were 2000µW/m2, 402µW/m2, 1262µW/m2 and 28µW/m2 in Arab Specialist hospital, Patient friends society, Salfeet hospital and Rafediya hospital respectively. The magnitude of electric field, magnetic field and the specific absorption rate (SAR) were calculated from the measured power flux density, which were less than the standard levels limitation of exposure to electromagnetic radiation EMR. The effect of EMR in operators health has been studied. Blood oxygen saturation (SPO2%), heart pulse rate (HPR), systolic blood pressure (SBP) and diastolic blood pressure (DBP) of the selected operators were measured before and after their shift, a significant impact does not appear in measured health parameter after exposure to EMR in radiology departments. Moreover, the measured values were within the standard values.

ركزت هذه الدراسة على البيئة الاشعاعية في بعض المراكز الصحية في فلسطين، حيث تم قياس مقدار الجرعة الناتجة من الاشعة السينية داخل غرفة التحكم وفي ممرات الانتظارعندما كانت الاجهزة تعمل وقورنت القيمة بالمعدلات المسوح بها من وزارة الصحة الفلسطينية حيث كانت جميع القراءات اقل من تلك القيمة. كما تم ايضا قياس كثافة جزيئات بيتا ومقدار الجرعة لاشعة جاما الناتجة من المصادر الطبيعية. كما تم قياس قيمة كثافة تدفق الطاقة في هذه المراكز, وقد كان معدل التدفق 2000 ميكروواط/ م2، 402 ميكروواط /م2، 1262 ميكروواط/م2 و28 ميكروواط/م2 في كل من المستشفى العربي التخصصي وجمعية اصدقاء المريض ومستشفى سلفيت ومستشفى رفيديا على الترتيب كما تم حساب قيمة كل من المجال الكهربائي والمجال المغناطيسي ومقدار كمية امتصاص انسجة الدماغ للطاقة بالاعتماد على قيمة معدل التدفق. تم دراسة تاثير الاشعة الكهرومغناطيسية في المراكز الصحية المدروسة على بعض المؤشرات الصحية للعاملين في مجال الاشعة, حيث تم قياس تشبع الدم بالاكسجين, ومعدل ضربات القلب, وضغط الدم الشرياني الانقباضي والانبساطي قبل بدء الموظف بالعمل وعند لانتهاء في الفترة الصباحية على مدى ثلاثة ايام مختلفة حيث اخذت معدل القراءات لكل موظف, لوحظ ان المؤشرات الصحية السابقة بقيت ضمن الحدود الطبيعية بعد التعرض للاشعاع في قسم الاشعة.
البيئة الاشعاعية في مراكز صحية مختارة في فلسطين